A Meta-Analysis of the Outcomes of Split-Thickness Skin Graft on Diabetic Leg and Foot Ulcers. (March 2019) - Yammine, Kaissar; Assi, Chahine
Diabetic lower limb ulcers are a serious complication to diabetes that could lead to amputation and death. Split-thickness skin graft (STSG) has been proposed by some authors to treat noninfected diabetic wounds, mainly those found in the leg and on the dorsum of the foot. No quantitative evidence synthesis over this technique has been reported in the literature. The study is a meta-analysis on the effectiveness of STSG in treating diabetic leg and foot ulcers. Electronic databases were searched from inception. No limitation was imposed on study design. Eleven studies comprising 757 patients with 759 foot/leg ulcers were included. After a mean period of 2 years, 85.5% (95% confidence interval [CI] = 0.766-0.925) of ulcers were healed over a mean time of 5.35 ± 2.25 weeks, with a recurrence rate of 4.2% (95% CI = 0.009-0.096), an infection rate of 4.4% (95% CI = 0.013-0.092), and a regrafting rate of 12.1% (95% CI = 0.053-0.212). Infection was the only reported donor site morbidity with a frequency of 1.74% (95% CI = 0.001-0.048). These weighted values are found to be noticeably superior to those reported in the literature following standard conventional care. The results of the review make STSG the ideal method to treat noninfected recurrent or recalcitrant ulcers of the leg and dorsal foot. Furthermore, the authors argue that STSG should be used more frequently in the management of such wounds. The findings should encourage future prospective investigations.